Motivation and resistance as predictors of sports practice expectations: a case study of the Physical and Sports Activity students of the Central University of Ecuador (Motivaciones y resistencias, e imagen del profesorado de actividad física y deportiva - Jenny Esmeralda Martínez Benítez; LLuisa Aitana Sauleda Martínez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract: This study analyzes factors that may influence the expectations of practicing future sports. Among these factors, the motivation and resistance towards the practice of physical activity and sports from 300 students of the Central University of Ecuador are analysed. The metaphorical constructions of the students are also interpreted in relation to the impact that the physical activity and sports -PAS has in their personal lives. The metaphorical constructions of the students, in relation to the meaning that the PAS represents in their personal life are also considered and the students’ perception of their Physical activity and Sports teachers also is requested. Finally, the expectations of PAS practice that they express are taken into account. The methodology is qualitative with an interpretative approach. The data collection technique is an interview that allows you to understand the problem from the perspective of its protagonists. In the data processing, the Aquad 6 computer program is used, which allows the analysis of the narratives through categories and codes. The results show that motivation exceeds resistance, and that the lack of time is its great difficulty to practice. In the study of metaphors, the level of satisfaction indicated, coincides with the metaphors of the value of PAS in personal life as a source of well-being and health. The findings show high expectations which could be correlated with the positive satisfactions in practice, the image of the teaching staff and the vital relevance they attach to the PAS.